Reconstructing biblical Dead Sea scrolls : a new method applied to the reconstruction of 4QSama̳ - Herbert, Edward D. (Studies on the Texts of the Desert of Judah, 1997)
The first part of the book develops a battery of scientifically based tools to aid the reconstruction of biblical Dead Sea Scrolls, which, when applied together, substantially improve the quality of reconstruction attainable. The focus then moves to the important non-masoretic but fragmentary biblical scroll, 4QSamᵃ, for which sixty-two new fragment identifications and an analysis of the character of the scroll are presented. Based upon this, a detailed reconstruction of the 4QSamᵃ fragments of 2 Samuel is undertaken, revealing 55% more deviations from the Masoretic text than had previously been identified. The effectiveness of the new method is thus demonstrated. Data concerning the support of key Hebrew and Greek witnesses provides a valuable foundation for the study of the history and development of the biblical text.